Sorority organizations, their activities and member attitudes - Aquino, Leticia S. 1933- (1961)
Seven sorority organizations in the University of the Philippines are the subjects of this study. An analysis of the sorority constitutions and the extent to which they are followed or implemented are provided and determined. In terms of sorority objectives, membership, organizational set-up and dynamics, this identifies which constitutional provision needs to be discarded, modified or changed, and which needs to be preserved, strengthened, and made a part of the heritage of the University in general and the sorority in particular.
Appendices include constitutions of 7 sororities in the University of the Philippines.
Thesis (M.Ed.)--University of the Philippines, 1961
Keywords: Greek letter societies